Investigation of gap-closing interdigitated capacitors for electrostatic vibration energy harvesting. (14th September 2015) - Oxaal, John; Foster, Daniel; Hella, Mona; Borca-Tasciuc, Diana-Andra
Abstract: This paper reports on the dynamic characteristics of a MEMS electrostatic harvester employing interdigitated gap-closing topology. Devices are fabricated using SOIMUMPS technology and are characterized with and without biasing voltages for a broad range of excitation accelerations. At low vibration amplitudes the presence of a dc bias causes the resonant frequency peak to shift to lower frequencies with increasing bias. At higher vibration amplitudes the dynamic response of the devices exhibits the behavior of a Duffing oscillator with spring softening due to nonlinear stiffness attributed to the effect of electrostatic forces. Specifically, the devices exhibit sweep direction hysteresis with jump phenomena due to the multivaluedness of the response curve. Amplitude sweeps at constant frequency and varying bias voltage also show jump phenomena, highlighting how slight differences in operating conditions dramatically affect device performance. Spring hardening effects are reported for devices contaminated with dust particles. The paper also discusses SOIMUMPS limitations, the importance of reducing off-axis vibration during testing, characterization methods, and the effect of grounding on parasitic capacitance.